Reliability, validity and generalizability of multidimensional pain assessment tools used in postoperative adult patients: a systematic review protocol. (July 2019) - Lapkin, Samuel; Fernandez, Ritin; Ellwood, Laura; Diwan, Ashish
ABSTRACT: Objective: The objective of this review is to evaluate the measurement properties of multidimensional pain assessment tools for postoperative pain in adults. Introduction: Effective postoperative pain management increases patient safety and satisfaction, and reduces healthcare costs. The most commonly used postoperative pain assessment tools only evaluate pain intensity, which is only one aspect of the sensory dimension of pain. Pain is a subjective phenomenon, and variability exists among patients. Efforts are underway to incorporate multidimensional assessment tools for postoperative pain assessment in clinical practice. Inclusion criteria: Eligible studies will include postoperative patients aged 18 years and older from all surgical disciplines. Studies evaluating multidimensional assessment instruments for the measurement of postoperative pain during the first two weeks following surgery will be considered. Studies will include the following measurement properties of assessment tools as outcomes: reliability, validity and generalizability. Methods: MEDLINE, CINAHL, Embase, PsycINFO and Cochrane Trials (CENTRAL) will be searched, as well as ClinicalTrials.gov and multiple gray literature sources. There will be no limitations on publication date. Titles and abstracts will be screened by independent reviewers for inclusion. The full text of selected papers will be retrieved and assessed against the inclusion criteria. Two independent reviewers will assess papers for methodological quality using the COSMIN checklist, and papers with poor scores on relevant items will be excluded. Data will be extracted by two independent reviewers using a standardized data extraction tool. Statistical pooling will be performed, if possible.